Sesame Value Chain: A Climate-Smart Agriculture Approach - An Extension Workers Manual - Ministry of Agriculture, Animal Industry and Fisheries, Uganda (2023)
Sesame (locally known as simsim) production in Uganda is increasingly becoming popular because of its wide benefits. Sesame production is equally being affected by several factors including climate change. Climate change is associated with changing precipitation patterns, rising temperatures and prolonged dry spells. This manual therefore provides detailed information on sesame growing in times of climate change. The manual is structured in five chapters which are summarized as follows. Chapter one includes the overall introduction which comprises the background, the different context of sesame production, sesame marketing and uses. The chapter discusses the crop morphology and characteristics including the different growth and development stages. This section also highlights sesame production constraints in times of climate change. Chapter two discusses the concept of climate change and how it affects sesame production. It further defines climate change and illustrates its causes. The section also explains the effects of climate change, the trends of climate change over the years as well as the impact of climate change on sesame production. Chapter three expounds on the sesame production constraints in the face of climate change. The constraints include socio-economic constraints, economic constraints, agronomic constraints as well as environmental constraints. Chapter four explains sesame production practices and technologies. In this chapter, climate mart agriculture is defined, and its three pillars elucidated. The chapter also highlights the production practices, opportunities, and challenges in sesame farming. Chapter five introduces the reader to record keeping and record management in sesame production. The section highlights the importance of farm records, the characteristics of good records and types of farm records. The chapter includes an indicative cost benefit analysis to help determine profitability of sesame production. With the highlighted content, the manual will facilitate knowledge and skills transfer as a way of promoting adoption of climate smart agriculture (CSA) technologies and practices in sesame growing among farming communities